2012
DOI: 10.3233/ch-2012-1604
|View full text |Cite
|
Sign up to set email alerts
|

Viability and function of primary human endothelial cells on smooth poly(ether imide) films

Abstract: Poly(ether imide) (PEI) is being explored as potential biomaterial for cardiovascular applications.Different studies showed that human umbilical venous endothelial cells (HUVEC) are able to adhere and proliferate on PEI membranes (R q = 13.20 ± 1.58 nm). A recently published study revealed evidence for much lower platelet adhesion on very smooth PEI-films (R q = 2.37 ± 1.40 nm). Therefore, we explored whether primary human venous endothelial cells (HUVEC) are able to adhere and proliferate on such very smooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Although endothelial cells seeded on PEI films showed decreased cell density after 48 h, cells grew to confluence in long‐term seeding experiments. Analyses of cytoskeletal proteins proved a comparable formation of actin filaments and focal adhesions of endothelial cells on PEI films and on control surfaces, facilitating the development of proper cell–cell and cell–matrix interactions (Schulz et al ., ). Furthermore, it could be shown that cells on PEI films secreted lower amounts of the inflammatory cytokine IL‐6 compared to cells on control surfaces, indicating an anti‐inflammatory effect of the PEI material (Schulz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Although endothelial cells seeded on PEI films showed decreased cell density after 48 h, cells grew to confluence in long‐term seeding experiments. Analyses of cytoskeletal proteins proved a comparable formation of actin filaments and focal adhesions of endothelial cells on PEI films and on control surfaces, facilitating the development of proper cell–cell and cell–matrix interactions (Schulz et al ., ). Furthermore, it could be shown that cells on PEI films secreted lower amounts of the inflammatory cytokine IL‐6 compared to cells on control surfaces, indicating an anti‐inflammatory effect of the PEI material (Schulz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Analyses of cytoskeletal proteins proved a comparable formation of actin filaments and focal adhesions of endothelial cells on PEI films and on control surfaces, facilitating the development of proper cell–cell and cell–matrix interactions (Schulz et al ., ). Furthermore, it could be shown that cells on PEI films secreted lower amounts of the inflammatory cytokine IL‐6 compared to cells on control surfaces, indicating an anti‐inflammatory effect of the PEI material (Schulz et al ., ). These results suggest that PEI materials exhibit properties that point to good in vivo biocompatibility, making them potential implant biomaterials.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations